INDICATORS OF TECHNOLOGY IN THE PERCEPTION OF IT AND BUSINESS MANAGERS – A COMPARATIVE ANALYSIS - Salati Marcondes de Moraes, Gustavo Hermínio (2015)
In this study we sought to identify how the indicators of information technology use can assist in the information technology governance and alignment of organizations through benchmarking. Multiple case studies were conducted in four large organizations that act in the service sector of vocational education, in which information technology plays a key role, interviewing executives from technology and business. The main indicators used in the study where the index G (expenditure and investment in IT / annual net sales) and the CAPT (annual cost per keyboard). As a result, it became clear that the indicators are perceived as important for information technology governance and alignment, and their own quality management, integrating corporate governance. Therefore, the indicators presented serve as management tools and a basis of comparison with other companies, the sector of activity, as a comparison of the historical evolution's own internal organization (monitoring) and as part of negotiation for future technology investments, providing support to the information technology managers and business managers, facilitating their decisions.Keywords: Information technology. Indicators. IT governance.